FEMINISIM REPRESENTATION IN LOUISA MAY ALCOTT’S NOVEL LITTLE WOMEN - Berutu, Achmanuddin; Waradana, Fitra Andira; Ikbal, Muhammar; Siregar, Naufal Karim; Purwarno, Purwarno (SIGEH ELT : Journal of Literature and Linguistics, 2024)
Louisa May Alcott's Little Women, a seminal work in American literature, profoundly explores the roles, aspirations, and challenges faced by women in the 19th century. Set against the backdrop of the American Civil War and its aftermath, the novel follows the lives of the March sisters—Meg, Jo, Beth, and Amy—as they navigate the complexities of womanhood in a society governed by rigid gender norms. Through rich character development and a compelling narrative, Little Women offers insight into the evolving landscape of women's rights and feminist thought during a pivotal era in American history. This paper aims to analyze the representation of feminism in Little Women, examining how the novel both conforms to and challenges traditional gender expectations. Drawing on liberal, Marxist, existentialist, and radical feminist theories, the paper explores various aspects of the March sisters' experiences, shedding light on their pursuit of autonomy, independence, and self-determination. Through a comprehensive analysis of key passages and character dynamics, the study uncovers the ways in which Alcott's work contributes to the broader discourse surrounding women's rights and gender equality.